IN VITRO EVALUATION OF ANISOPUS MANNII AND LEPTADENIA HASTATA FOR ANTIBACTERIAL POTENTIAL AGAINST BACTERIAL ISOLATES FROM DIABETIC WOUND - Sani, Sakina B.; Usman, B. M.; Hayatu, M.; Hardiyya, A. Y.; Bilkisu, A.; Umma, M.; Mamadina, M. M.; Hassan, M. I.; Safiyanu, I.; Jibril, A.; Ajingi, Y. S.; Sale, A. I. (FUDMA JOURNAL OF SCIENCES, 2021)
Leptadenia hastata and Anisopus mannii – are perennial plants of family Asclepiadaceae. They are widely distributed in West Africa and are locally used as anti-diabetic agents in Northern Nigeria. This study was conducted to investigate the phytochemical constituent and antibacterial activity of the crude ethanol extract of the Leptadenia hastata and Anisopus mannii against some bacterial isolates from diabetic wound. The phytochemical screening was carried out using standard protocol and antibacterial activity was determined by agar well diffusion method followed by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) on the plant extract that showed activity. Result of phytochemical screening reveals the present of tannins, phenols, flavonols, saponins, and alkaloids in all the plants extract except in Anisopus mannii where alkaloid is absent. Also, result from antibacterial activity of leptadenia hastata demonstrated inhibition zones ranging from 11.5±0.71 to 20.0±0.00 at various concentrations (8mg/ml and 4mg/ml) against the tested organisms (Citrobacter specie, E.coli, Proteus vulgaris.) with MIC and MBC values ranging from 2mg/ml-8mg/ml. Hence, the ethanol extract of Leptadenia hastata can be considered as new therapeutic agent for the treatment of diabetic wound infection. Further studies need to be carried out to investigate toxicological effect and diabetic wound healing property of the plant.